The Readiness Of Shipping Companies In Tegal Region To Implement IMO Regulations In The Field Of Marine Pollution Prevention - Suryadi, Awel; Sunarso, Hadi (LPPM AKMI SUAKA BAHARI CIREBON, 2024)
Marine pollution that occurs due to ship waste increasingly threatens Indonesian waters. Sources of marine pollution are caused by shipping and port activities. Handling this pollution must be carried out with facilities and infrastructure holding marine pollution in accordance with international standards on board ships and at loading and unloading ports, so competent professionals are also needed in their fields. The purpose of this study is to determine and analyze the readiness of shipping companies in the Tegal region to face IMO rules in the field of marine pollution prevention. The study used qualitative description methods by conducting observations, interviews, and literature. Based on the results of the research, it was found that the problem that occurred was administrative; companies related to human resources could meet competencies. Shipping agents in the Tegal area are limited to serving ship document management, while the procurement or repair of pollution prevention equipment is under the authority of the ship owner through his representative, who will conduct a survey when the ship carries out docking/repair at TUKS or Tersus. There are still docking companies that handle the remaining sludge waste from OWS, which is landfilled, so if it accumulates a lot, it can cause soil pollution. The lack of public awareness and limited facilities and infrastructure for ship waste management in the port area are problems for the government and other stakeholders at the port.